On the transition probabilities confidence interval evaluation in the syndromic analysis - Algimantas Bikelis; Sigitas Dapkūnas; Mečislovas Meilūnas; Danutė Stoškuvienė (Lietuvos Matematikos Rinkinys)
A confidence interval evaluation problem of transition probabilities is considered.